Primary Breast Sarcoma: A Two-Centre Analysis and Review of Literature - Žatecký, Jan; Coufal, Oldřich; Fabian, Pavel; Holánek, Miloš; Sehnálková, Eva; Burkoň, Petr (Breast care (Basel, Switzerland), 2023)
INTRODUCTION: Primary breast sarcoma is a very rare malignant type of breast tumours with an incidence of 0.1% of all primary breast malignancies. METHODS: We present a retrospective analysis of the case series from two hospitals in the Czech Republic with a review of the diagnostic and treatment approach to primary breast sarcomas with an analysis of published prognostic factors. RESULTS: Eleven patients were included in the study, 9 women and 2 men. Statistical evaluation revealed that tumour size (p = 0.1964), grade (p = 0.1667), margin distance (p = 0.5403), mitotic activity (p = 0.8577), or age (p = 0.7822) were not prognostic factors in our cohort. CONCLUSION: The analysis did not prove any of the factors, such as age, tumour size, grade, or mitotic activity, to be statistically significant prognostic factors. Based on the literature review, the most common published prognostic factors are tumour size, margin status, and grade, but the results are ambiguous.
Keywords: Primary breast sarcoma; Prognostic factors; Two-centre analysis